Ostrich Eggshell as an Alternative Source of Calcium Ions for Biomaterials Synthesis - Caliman,Lorena Batista (2017)
Ostrich eggshells are a potentially abundant and a high purity and low cost source of calcium to produce β-Tricalcium Phosphate (β-TCP) and Hydroxyapatite (HA), important calcium phosphates used as biomaterials. Here, we use a wet precipitation procedure to synthesize these phosphates using ostrich eggshells as a source of calcium ions. The biphasic precipitated powder, calcined at 800ºC, is a mixture of both Hydroxyapatite and β-Tricalcium Phosphate, also known as the biomaterial Biphasic Calcium Phosphate (BCP). Physico-chemical properties of the final powder product show water and CO32- groups absorbed in the particles surface, 0.1 to 100 µm particles size distribution and 11.70 m2/g of specific surface area.